High-intensity intermittent aeration with multi-stage descending rates enhances oxygen uptake to mitigate nitrogen emissions and promote humification in composting - Ruolan Tang; Ruonan Ma; Kaishu Luo; Yifan Zhai; Bin cui; Fanqiao Meng; Guoxue Li; Yue Xie; Jing Yuan (Journal of Cleaner Production, 2026)

Aerogels in active packaging for food preservation: A comprehensive review of applications - Chen Chen; Yujian Zhang; Huijun Cui; Ke Wu; Ruonan Guo; Aili Jiang; Di Wu (Trends in Food Science & Technology, 2026)

Potential use of plasma-activated water cleaning for aflatoxin B1 degradation in peanuts - Ruonan Ma; Cui Xu; Junxia Feng; Hangbo Xu; Yongqin Fan; Guoyu Zhou; Ximei Dai; Dongjie Cui; Zhen Jiao (Food Chemistry, 2025)

The Identification and Synthesis of New Sea Cucumber Peptides Leveraging Peptidomics Technology, along with their Anti-Parkinson’s Disease Efficacy - Jiawei Liu; Yusheng Shi; Lingling Jin; Baixue Sun; Ruonan Wang; Guangbo Ge; Guanghao Zhu; Xiaolin Cui; Jie Zhao; Yan Zhang; Sheng Li (Journal of Neuroimmune Pharmacology, 2025)

Carbon dots promote tomato growth and yield via photosynthesis enhancement and leaf senescence delay - Shuang Li; Wenbo Zhao; Wei Zhao; Zhen Jiao; Keqiao Cui; Rong Wang; Aiying Wang; Yuantao Tan; Huandong Li; Yue Yin; Feijuan Gao; Kaikai Liu; et al. (Journal of Plant Physiology, 2025)

Optimizing organic waste co-composting: Component ratio thresholds for dual enhancement of maturity and gaseous emission reduction - Ruonan Ma; Ruolan Tang; Guannan Zheng; Jiani Wang; Zhongliang Cui; Yan Liu; Guoxue Li; Fanqiao Meng; Jing Yuan (Journal of Environmental Chemical Engineering, 2025)

Cold atmospheric plasma-derived ROS detoxifies deoxynivalenol-induced nephrotoxicity - Ruonan Ma; Junxia Feng; Hangbo Xu; Xiaoying Zhou; Chunli Liu; Guoyu Zhou; Dongjie Cui; Yupan Zhu; Junhu Wan; Dezheng Yang; Gautam Sethi; Xudong Yang; et al. (Journal of Hazardous Materials, 2025)

Dual-modality Encoder-decoder Framework for Urban Real-time Rainfall-runoff Prediction - Yuan Tian; Ruonan Cui; Wenlong Fu; Zhenyu Ao; Qi Han; Yi Xiang; Xinyu Lei (Water Resources Management, 2025)

Urban real-time rainfall-runoff prediction using adaptive SSA-decomposition with dual attention - Yuan Tian; Wenlong Fu; Yi Xiang; Qian Xiong; Ruonan Cui; Zhenyu Ao; Xinyu Lei (Journal of Hydrology, 2025)

Global to local: a novel encoder-decoder framework for urban real-time rainfall-runoff forecasting - Yuan Tian; Wenlong Fu; Yajing Dong; Qi Han; Qian Xiong; Ruonan Cui; Zhenyu Ao; Xinyu Lei (Earth Science Informatics, 2025)

Characterization of differences in physicochemical properties, volatile organic compounds and non-volatile metabolites of prune wine by inoculation of different lactic acid bacteria during malolactic fermentation - Jianqiao Jiang; Yun Xie; Miao Cui; Xiaomei Ma; Ruonan Yin; Yiwen Chen; Yongkang Li; Yue Hu; Weidong Cheng; Feifei Gao (Food Chemistry, 2024)

Effects of thermophilic bacteria inoculation on maturity, gaseous emission and bacterial community succession in hyperthermophilic composting - Jing Zhang; Yilin Kong; Yan Yang; Ruonan Ma; Guoxue Li; Jiani Wang; Zhongliang Cui; Jing Yuan (Science of The Total Environment, 2024)

Dynamic changes of physicochemical parameters, antioxidant activity, organic acids, polyphenols, and volatile components in prune vinegar during fermentation - Ruonan Yin; Jianqiao Jiang; Xiaomei Ma; Yun Xie; Miao Cui; Yiwen Chen; Yongkang Li; Yue Hu; Weidong Cheng; Feifei Gao (Food Bioscience, 2024)

Higher visceral adipose tissue is associated with decreased memory suppression ability on food-related thoughts: A 1-year prospective ERP study - Ke Cui; Jia Zhao; RuoNan Li; Yuan Gao; Xiao Gao (Appetite, 2023)

A novel antibacterial mechanism of atmospheric cold plasma against Staphylococcus aureus through degradation of cellular staphyloxanthin - Yupan Zhu; Hangbo Xu; Dongjie Cui; Renwu Zhou; Yanping Wang; Aswathi Soni; Gale Brightwell; Jie Zhuang; Ruonan Ma; Zhen Jiao (Innovative Food Science & Emerging Technologies, 2023)

Data‐driven estimation of nitric oxide emissions from global soils based on dominant vegetation covers - Xingshuai Tian; Yulong Yin; Kai He; Ruonan Qiu; Jiahui Cong; Zihan Wang; Huitong Yu; Zhong Chen; Yiyan Chu; Hao Ying; Zhenling Cui (Global Change Biology, 2023)
Soils are a major source of global nitric oxide (NO) emissions. However, estimates of soil NO emissions have large uncertainties due to limited observations and multifactorial impacts. Here, we mapped global soil NO emissions, integrating 1356 in‐situ NO observations from globally distributed sites with high‐resolution climate, soil, and management practice data. We then calculated global and national total NO budgets and revealed the contributions of cropland, grassland, and forest to global soil NO emissions at the national level. The results showed that soil NO emissions were explained mainly by N input, water input and soil pH. Total above‐soil NO emissions of the three vegetation cover types were 9.4 Tg N year −1 in 2014, including 5.9 Tg N year −1 (1.04, 95% confidence interval [95% CI]: 0.09–1.99 kg N ha −1 year −1 ) emitted from forest, 1.7 Tg N year −1 (0.68, 95% CI: 0.10–1.26 kg N ha −1 year −1 ) from grassland, and 1.8 Tg N year −1 (0.98, 95% CI: 0.42–1.53 kg N ha −1 year −1 ) from cropland. Soil NO emissions in approximately 57% of 213 countries surveyed were dominated by forests. Our results provide updated inventories of global and national soil NO emissions based on robust data‐driven models. These estimates are critical to guiding the mitigation of soil NO emissions and can be used in combination with biogeochemical models.

Study of the adsorption behavior of tetracycline onto suspended sediments in the Yellow River, China: Insights into the transportation and mechanism - Quantao Cui; Jiawei Liu; Yifan Tang; Yao Ma; Gong Lin; Ruonan Wang; Wei Zhang; Qiting Zuo; Xiaoli Zhao; Fengchang Wu (Science of The Total Environment, 2023)

Bioinspired gradient structured soft actuators: From fabrication to application - He Liu; Ruonan Liu; Kun Chen; Yiying Liu; Yue Zhao; Xiaoyu Cui; Ye Tian (Chemical Engineering Journal, 2023)

Warming of surface water in the large and shallow lakes across the Yangtze River Basin, China, and its driver analysis - Jing Li; Jingjing Sun; Ruonan Wang; Tiejun Cui; Yindong Tong (Environmental Science and Pollution Research, 2022)

Quantitative analysis of lake-cooling effect in Hefei City, China, based on multispectral remote sensing and its response to urban expansion - Xuening Lin; Yuhuan Cui; Shuang Hao; Hong Hong; Man Zhang; Jingdong Zhang; Ruonan Li; Mengyu Liu (Environmental Science and Pollution Research, 2022)